Lodos ativados aplicados no tratamento de esgoto doméstico e industrial: avaliação de duas ETEs localizadas no município de Juiz de Fora - MG - Diniz, Renata Borges (2021)
The population increase in Brazil, added to the development of industries, especially in medium-sized cities, has provided greater water consumption. Thus making it an aggravating factor in the dynamics of domestic and industrial sewage treatment units due to the large volumes generated, requiring the improvement of the units and constant evaluation of the final quality of raw and treated sewage through efficient treatment in small areas. The activated sludge treatment technology has a wide range of operations throughout the world, constituting aerated treatment units capable of producing better quality final sewage. In this context, the efficiency of the domestic sewage treatment plants ETE1 Barbosa Lage and industrial sewage at ETE2 Barreira do Triunfo, located in the municipality of Juiz de Fora – MG, was evaluated during one year of monitoring. Both systems are composed of an equalization tank, responsible for the homogenization of wastewater; prolonged aeration tank (reactor) where biochemical reactions remove organic and nitrogen matter occur; and a secondary decanter for sedimentation of solids, allowing for better quality sewage. The evaluation of the pollutants removal efficiency was carried out through the physical, chemical and biological variables, COD, BOD, SD and SST, measured at the entrance and exit of the systems, during the months of January to December 2018. It was observed that ETE1 had an average removal of 71, 85 and 71% of COD, BOD and SST, respectively, from domestic sewage, a result lower than that observed for ETE2 with industrial sewage. Efficiencies for all industrial sewage quality variables analyzed were greater than 90%, resulting in an average output concentration for COD of 39.83 mg L-1 during one year of monitoring. ETE2 Barreira do Triunfo reached CONAMA 357/2005 launch standards; 430/2011 and COPAM 01/2008 for all variables analyzed throughout the year. Despite the ETE1 Barbosa Lage presenting values in September for the COD of 475 mg L-1, above the limit established by COPAM no 01/2008, its annual removal efficiency was superior to the established minimum, by 71%. According to the limits established by COPAM no 01/2008, BOD was higher by 13 and 4.6 mg L-1 in the months of June and October. SST and SD also had monthly values that exceeded the established limits. The performance of activated sludge treatment was superior for all variables for industrial sewage, when compared to domestic sewage.